Cathepsin B: A controversial target for alzeihmer's disease - YADAV M,; AVASTHI A S, (International Journal of Pharma and Bio Sciences, 2017)
Alzheimer’s disease (AD) is an irreversible progressive neurodegenerative disorder, with unresolved etiology and is characterized by the long latency between the initial dysregulation processes and the late appearance of clinical symptoms. It slowly leads to loss in memory, thinking skills, visuospatial orientation, judgement and personality and eventually the person becomes profoundly mute, disabled and immobile. Amyloid beta (Aβ) generation is the critical initiating event for the development of AD. Cathepsin B (CatB) is an established biomarker for AD. However, its therapeutic role still needs further investigation. Some studies suggest that the CatB act as an anti-amyloidogenic agent via C-terminal degradation of Aβ peptides, and hence CatB inhibition increases Aβ levels and plaque deposition. While other studies suggest that CatB inhibition or knockout reduces Aβ levels and improves memory deficit in AD patients. This review highlights recent studies focussing on the role of CatB in progression or inhibition of AD.